Influence of temperature on the electro-induced MIT of VO2 prepared by the magnetron sputtering method - Sun,Xiaoning (2021)
ABSTRACT Vanadium dioxide (VO2) is a typical representative of the strongly correlated electronic system. It presents a reversible first-order metal-insulator transition once stimulated by temperature, voltage, light, or pressure. The insulation-metal phase transition (MIT) makes it a new type of functional material with excellent potential applications in many fields. In this paper, magnetron sputtering technology and the "two-step method" process are used to prepare the VO2 films with phase transition properties. The results show that after the classic V film is processed for more than 100 minutes in air, and annealed in N2 atmosphere for 150 minutes, the VO2 (M) can be obtained with a resistance change rate more than three orders of magnitude. The study of the resistance change under the action of temperature and voltage found that the temperature of the heating and cooling phase transition are 67.4ºC and 62.8ºC respectively, and the hysteresis width is 4.6ºC. The relationship between phase transition voltage and ambient temperature is presented based on the heat dissipation model. It is found that Joule heating plays a significant role in the electro-induced phase transition of VO2. Furthermore, the ambient temperature has an obvious regulation effect on the phase transition voltage of VO2 film. The research results can provide efficient guidance to the preparation of VO2 film and the application and regulation of electro-induced phase transition.